Making and monitoring errors based on altered auditory feedback - Pfordresher, Peter Q.; Beasley, Robertson T. E. (Frontiers in Psychology, 2014)
Previous research has demonstrated that altered auditory feedback (AAF) disrupts music performance and causes disruptions in both action planning and the perception of feedback events. It has been proposed that this disruption occurs because of interference within a shared representation for perception and action (Pfordresher, 2006). Studies reported here address this claim from the standpoint of error monitoring. In Experiment 1 participants performed short melodies on a keyboard while hearing no auditory feedback, normal auditory feedback, or alterations to feedback pitch on some subset of events. Participants overestimated error frequency when AAF was present but not for normal feedback. Experiment 2 introduced a concurrent load task to determine whether error monitoring requires executive resources. Although the concurrent task enhanced the effect of AAF, it did not alter participants’ tendency to overestimate errors when AAF was present. A third correlational study addressed whether effects of AAF are reduced for a subset of the population who may lack the kind of perception/action associations that lead to AAF disruption: poor-pitch singers. Effects of manipulations similar to those presented in Experiments 1 and 2 were reduced for these individuals. We propose that these results are consistent with the notion that AAF interference is based on associations between perception and action within a forward internal model of auditory-motor relationships.